Inside the Clinton White House : an oral history - Riley, Russell L. 1958- (Oxford oral history series, 2016)
"In the decade after Bill Clinton left the White House, scores of his closest aides recorded interviews with the University of Virginia's Presidential Oral History Program. The contents of these interviews are published for the first time in this volume. Based on 400 hours of candid conversations, Inside the Clinton White House adds color and nuance to our understanding of Bill Clinton and his administration"...